Engaging practitioners as co-researchers in national policy evaluations as resistance to patriarchal constructions of expertise: The case of the end of year three evaluation of the access and inclusion model - Sheridan, Denise; Robinson, Deborah; Codina, Geraldene; Gowers, Sofia J.; O’Sullivan, Lisha; Ring, Emer (Frontiers in Education, 2022)
Seventeen Practitioner Researchers (PRs) were engaged as co-researchers in an evaluation commissioned by Ireland’s Department of Childhood, Equality, Disability, Integration, and Youth (DCEDIY), as an innovative aspect in methodological design. The evaluation investigated the implementation and impact of Ireland’s award winning policy for the inclusion of children with disabilities in mainstream pre-schools, the Access and Inclusion Model (AIM). As co-researchers in the project, the PRs constructed case studies of pre-schools, and children who were being supported by AIM. In this context, this paper draws on feminist theory to present the rationale for involving PRs as co-researchers in evaluations of high profile national programs like AIM. It also applies thematic analysis to a critical reflection written by one co-researcher (who is also the lead author), in which she writes about her gendered experience of being a PR. Thematic Analysis (TA) is applied to this critical reflection to explore the way in which the PR role may have impacted on her professional identity and agency. Three themes were constructed from the TA which included expertise as a resource for advocacy, personal and professional development, and continual learning and inclusive practice. The findings were interpreted through a feminist lens, and cast light on the way that the PR frames professional potency within more feminine constructions of power related to care, nurture, collaboration, nurturing and enabling. They also demonstrate how, in this particular case, the PR role had a transformative impact on expert identity, and enriched capitals for empowering others. The paper ends with a call for more participative approaches to the evaluation of national policies through the engagement of practitioners as researchers. It is argued that this would result in evaluations that were more attuned to the vernacular of practice, and hence more impactful. It also offers opportunities for professional development whilst symbolizing the validation of practitioner expertise by policy makers in a feminized sector where, low pay and low status have long been issues of concern.